2019
DOI: 10.4238/gmr18269
|View full text |Cite
|
Sign up to set email alerts
|

Research Article The <i>eNOS</i> T786C polymorphism is not related to atherosclerosis and cofactors in a Brazilian population

Abstract: ©FUNPEC-RP www.funpecrp.com.br Genetics and Molecular Research 18 (3): gmr18269 F.R.B. Oliveira et al. 2 association was found between smoking and eNOS T786C polymorphism. As for drinking, there was also no association with this polymorphism and or with cofactors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…In our study, the genotype frequency of eNOS T786C polymorphism showed a 2.3fold higher incidence of TC genotypes in relation to the mutant genotype (CC) in the experimental and control groups. This result is similar to the findings of Barbosa et al (2017), Silva (2019) and Oliveira et al (2019). They found a higher prevalence of the TC genotype in patients with atherosclerosis in the Brazilian population.…”
Section: Discussionsupporting
confidence: 90%
“…In our study, the genotype frequency of eNOS T786C polymorphism showed a 2.3fold higher incidence of TC genotypes in relation to the mutant genotype (CC) in the experimental and control groups. This result is similar to the findings of Barbosa et al (2017), Silva (2019) and Oliveira et al (2019). They found a higher prevalence of the TC genotype in patients with atherosclerosis in the Brazilian population.…”
Section: Discussionsupporting
confidence: 90%